2003
DOI: 10.1046/j.1365-2672.94.s1.10.x
|View full text |Cite
|
Sign up to set email alerts
|

Overland flow transport of pathogens from agricultural land receiving faecal wastes

Abstract: Considerable investment has been made in recent years in improvements to the microbiological quality of urban wastewater discharges to surface waters, particularly in coastal towns, with the aim of reducing the exposure of bathers and surfers to gastrointestinal pathogens. As this source of pollution has come under greater control, attention has started to focus on diffuse catchment sources of faecal contamination which have been shown to be dominant during high river flows associated with storm events. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(173 citation statements)
references
References 33 publications
4
153
0
2
Order By: Relevance
“…Based on empirical pathogen transportation models, detachment and transportation of pathogens from soils are minimised by reducing the size and velocity of water particles striking the soil (Tyrrel & Quinton 2003). Caps at watering can outlets reduce the size of irrigation water particles, and lower irrigation heights reduce the soil-striking velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Based on empirical pathogen transportation models, detachment and transportation of pathogens from soils are minimised by reducing the size and velocity of water particles striking the soil (Tyrrel & Quinton 2003). Caps at watering can outlets reduce the size of irrigation water particles, and lower irrigation heights reduce the soil-striking velocities.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies of manure-derived bacteria in soils show higher survival rates in NT soils compared to CP soils (Tyrrel and Quinton 2003;Hutchison et al, 2004;Rogers and Haines, 2005), other studies have reported little impact from tillage on soil bacteria concentrations after PM application. For example, Jenkins et al (2008) found no differences between EC concentrations in soil samples from CP and NT plots one day after poultry litter application and rainfall simulation.…”
Section: Effects Of Tillagementioning
confidence: 99%
“…The generally lower sediment losses associated with no-tillage result in a lower total phosphorus loss than conventional tillage. It is likely that pathogen load will also be reduced with reduced sediment losses (Tyrrel and Quinton, 2003).…”
Section: Stevens and Quinton 2009 Physics And Chemistry Of The Earth mentioning
confidence: 99%